1982
DOI: 10.1128/iai.38.3.1154-1163.1982
|View full text |Cite
|
Sign up to set email alerts
|

Surface receptors for serum albumin in group C and G streptococci show three different types of albumin specificity

Abstract: A total of 100 bacterial strains were tested for binding uptake of radiolabeled albumin preparations from 15 mammalian species. Three types of surface structures with specific binding sites for albumin were defined. A previously described receptor for albumin was separated into type a in Streptococcus equisimilis strains and in human group G streptococcal strains and type b in bovine group C streptococci. A new type of albumin receptor, type c, was found in Streptococcus dysgalactiae strains, the only receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…These authors found group A streptococci to interact with murine serum albumin, and to a lesser degree with HSA. In contrast, various group C and G streptococci displayed a high binding of HSA as well as the albumin of a number of mammalian species (15,24,25). The present results suggest that aggregation of HSA may facilitate detection of reactivity with streptococci.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These authors found group A streptococci to interact with murine serum albumin, and to a lesser degree with HSA. In contrast, various group C and G streptococci displayed a high binding of HSA as well as the albumin of a number of mammalian species (15,24,25). The present results suggest that aggregation of HSA may facilitate detection of reactivity with streptococci.…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, the finding that fibrinogen binds to most or all group A streptococci (2) indicates that M-protein epitopes both distinct from and identical with those binding a*HSA may bind fibrinogen. By contrast, in group C and G streptococci no common sites binding HSA and fibrinogen have been found (24). It is unknown at present whether the interaction with a*HSA may in some way be related to streptococcal pathogenicity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to IgG, some group C and G streptococci also have an affinity for albumin preparations of various origins (WIDEBACK and KRONVALL, 1982). According to and AKERSTROM et al (1987), protein G appears to be a bifunctional receptor molecule capable of binding to both IgG and serum albumin.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions are mediated by binding structures on the bacterial surface. Albumin-specific surface receptors are found on group A, C and G streptococci (13,19,29,30,31). The receptors for albumin are sterically different from all other described receptors on streptococci, e.g., albumin binds to the bacterial cell independently of other proteins.…”
mentioning
confidence: 99%